The Analysis of Indoor Air Pollutants From Finishing Material of New Apartments at Business Bay, Dubai - Jung, Chuloh; Al Qassimi, Nahla; Arar, Mohammad; Awad, Jihad (Frontiers in Built Environment, 2021)
Due to fast economy development, Dubai had built many high-rise apartments in short period of time. The Dubai Municipality regulates the indoor air quality with rigid regulation, but the de-tailed provisions are still not comprehensive. The objective of this paper is to conduct on-site measurements for new high-rise apartments before moving in to investigate indoor air pollution and to analyze pollutant emissions by type of finishing material. As a methodology, on-site measurements are conducted for 3 different housing units before moving in to investigate the status of indoor air pollution in new apartments. Based on the on-site measurements data, a lab experiments with small chamber for the same finishing materials from the most polluted housing unit were conducted to measure the emission of pollutants in 30 days. The result had shown that CH2O was lower than the standard (100 µg/m3) in all units, while TVOC (Total Volatile Organic Compound) exceeded the standard (500 μg/m3) in most of the units. It was proven that regarding the CH2O, silk wallpaper, initial wallpaper, & wallpaper adhesive had the highest emission and for the TVOC, tile & tile adhesive had the highest emission. During small chamber experiment, CH2O and TVOC emissions tended to decrease gradually over time, but the emission amount changed significantly in high pollutant emission material especially from day 1 to 10. Therefore, Dubai municipality should establish the regulation for residents to move into their new apartment after at least 10 days to avoid the high polluted emission from the curing process of the interior finishing material.